Analisis Kinerja Keuangan Perusahaan Makanan Dan Minuman Sebelum Dan Selama Pandemi Covid-19 - Yusuf Akbar, Muhammad Rifky; Sukoharsono, Eko Ganis (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to compare the financial performance of food and beverage subsector companies before and during the Covid-19 pandemic measured by financial ratios. The population in this study include all food and beverage subsector companies listed on the Indonesia Stock Exchange between 2019 and 2020, from which the samples of 18 companies are selected through purposive sampling. As the results of the Kolmogorov-Smirnov normality test exhibits that the data in this study are not normally distributed, a non-parametric test, called wilcoxon signed rank test, is conducted. The results of this study indicate that financial performance as measured by Return On Equity (ROE), Net Profit Margin (NPM), and Total Asset Turnover (TATO) shows significant differences before and during the Covid-19 pandemic, whilst, this is not the case for financial performance as measured by Current Ratio (CR) and Debt to Equity Ratio (DER).